Ordering signed graphs with large index - Brunetti, Maurizio (Ars mathematica contemporanea, 2022)
The index of a signed graph is the largest eigenvalue of its adjacency matrix. We establish the first few signed graphs ordered decreasingly by the index in classes of connected signed graphs, connected unbalanced signed graphs and complete signed graphs with a fixed number of vertices.
Keywords: adjacency matrix; complete signed graph; edge relocation; largest eigenvalue; matrika sosednosti; največja lastna vrednost; neuravnotežen predznačeni graf; polni predznačeni graf; povezavna premestitev; unbalanced signed graph